2022
DOI: 10.1136/bmjno-2022-000328
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of botulinum toxin type a in the targeted treatment of sleep bruxism: a double-blind, randomised, placebo-controlled, cross-over study

Abstract: BackgroundIntramuscular injections of botulinum toxin A (BTX-A) have been used in the treatment of sleep bruxism (SB) however controlled trials are limited and the optimal injection strategy and dose is not known.MethodsThis double-blind, randomised, placebo-controlled, cross-over study evaluated the efficacy and safety of BTX-A in participants with SB. Average bruxism events per hour of sleep (Bruxism Index, BI) was calculated using surface electromyography. Participants with BI >5 were included and random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…1 week in three RCTs, 14,23,24 2 weeks in one RCT, 14 1 month in seven RCTs, 8,14,22,23,[27][28][29] 2 months in two RCTs, 14,26 3 months in four RCTs, 8,14,22,24 6 months in four RCTs, 9,14,23,24 and 6 years in one RCT. 10…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 93%
See 4 more Smart Citations
“…1 week in three RCTs, 14,23,24 2 weeks in one RCT, 14 1 month in seven RCTs, 8,14,22,23,[27][28][29] 2 months in two RCTs, 14,26 3 months in four RCTs, 8,14,22,24 6 months in four RCTs, 9,14,23,24 and 6 years in one RCT. 10…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 93%
“…Twelve studies involving 158 participants reported adverse eve nts. 8,14,16,17,22,23,[25][26][27][28][29][30] There was no significant difference in the risk of any adverse effects between BTX-A and placebo (RR 2.68, 95% CI 0.86 to 8.35, p = .09, I 2 = 47%) (Figure 5). Subgroup analyses based on dosage and injection sites showed no difference compared to placebo and between subgroups (Figure S6).…”
Section: Adverse Effectsmentioning
confidence: 99%
See 3 more Smart Citations